Low-Dose Berberine Attenuates the Anti-Breast Cancer Activity of Chemotherapeutic Agents via Induction of Autophagy and Antioxidation. Issue 4 (8th October 2020) - Han, Bing; Wang, Kai; Tu, Yanbei; Tan, Lihua; He, Chengwei
Berberine (BBR), a major active component of Rhizoma coptidis, is one of the most promising agents for breast cancer adjuvant therapy. It is well accepted that BBR could exhibit remarkable anticancer efficacy with few side effects, and when treated with chemotherapeutic agents in combination, BBR could enhance the chemosensitivity of cancer cells. Our previous study reported that low-dose BBR (LDB) induced hormetic effect and attenuated the anticancer activity of chemotherapeutic agents. However, the underlying mechanisms are still unclear. In this study, we confirmed that LDB could promote cancer cell proliferation and antagonize the anti-breast cancer activities of chemotherapeutic agents. And the mechanisms were proved to be induction of autophagy and antioxidation by LDB. Our results showed that LDB could mildly induce reactive oxygen species, raise the level of autophagy by promoting the phosphorylation of adenosine monophosphate-activated protein kinase, and promote antioxidant enzymes expression through activating nuclear factor erythroid 2-related factor 2 in breast cancer cells. These findings revealed a potential negative impact of BBR on its adjuvant anti-breast cancer therapy, providing guidance for a safe and effective use of naturally originated medicines in the clinic.